Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Berbantuan Media 3 Dimensi Online (Assemblar Edu) Terhadap Hasil Belajar Siswa : (The Influence Of The Cooperative Learning Model Of The Two Stay Two Stray (TSTS) Type Assisted By 3D Online Media (Assemblar Edu) On The Learning Outcomes) - May, Florence Rambu; Bano, Vidriana Oktoviana; Huda, Marleni Rosalia Ndapa (BIODIK, 2026)
This study aims to describe the influence of the Two Stay Two Stray (Ts-Ts) Cooperative Learning Model Assisted by 3-Dimensional Online Media (Assemblar Edu) on the learning outcomes of class IX students at Muhammadiyah Waingapu Middle School. The sample in this study was 34 ninth-grade students, divided into two classes in the odd semester of the 2025/2026 academic year. The average posttest score for the experimental class was 80.58, higher than the average score for the control class, which was 75.36, with an average increase of 15.64 points in the experimental class. This is proven by the results of the hypothesis test using the Paired Sample t-test with a Sig. (2-tailed) value = 0.000 < 0.05, which indicates a significant difference between the pretest and posttest scores after the learning treatment was given. These results indicate that the use of the TS-TS model assisted by Assembalr Edu media is more influential than the Discovery Learning model. Abstrak. Penelitian ini bertujuan untuk mendeskripsikan Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (Ts-Ts) Berbantuan Media 3 Dimensi Online (Assemblar Edu) Terhadap Hasil Belajar Siswa Kelas IX Di SMP Muhammadiyah Waingapu. Sampel dalam penilitian adalah siswa Kelas IX yang berjumlah 34 orang dan terbagi dalam 2 kelas pada semester ganjil tahun ajaran 2025/2026. Nilai rata-rata hasil posttest kelas eksperimen sebesar 80,58 lebih tinggi dibandingkan kelas kontrol sebesar 75,36, dengan peningkatan rata-rata sebesar 15,64 poin pada kelas eksperimen. Hal ini dibuktikan melalui hasil uji hipotesis menggunakan Paired Sample t-test dengan nilai Sig. (2-tailed) = 0,000 < 0,05, yang menunjukkan adanya perbedaan signifikan antara nilai pretest dan posttest setelah perlakuan pembelajaran diberikan. Hasil ini menunjukkan bahwa penggunaan model TS-TS berbantuan media Assemblar Edu lebih berpengaruh dibandingkan dengan model Discovery Learning.